Clinical, Laboratory, Radiologic and Ex Juvantibus Diagnosis of Pediatric Scurvy: Diagnosis of Pediatric Scurvy - Sawitri; Hidayati, Afif Nurul; Bintanjoyo, Lunardi; Gunawan, Prastiya Indra; Noviandi, Riza; Widia, Yuri; Citrashanty, Irmadita; Zulkarnain, Iskandar (Journal of Pakistan Association of Dermatologists, 2022)
Background: Scurvy or vitamin C deficiency is uncommon in children. Scurvy has nonspecific initial manifestations of fever, decreased appetite and irritability. It is followed by musculoskeletal findings such as arthralgia, joint swelling and pseudoparalysis, which are more prominent than dermatological findings such as follicular hyperkeratosis, skin and mucosal bleeding. Pediatric scurvy is often misdiagnosed as rheumatic diseases. Ascorbic acid level determination is gold standard diagnosis for scurvy, but not always available. Methods: This case report highlighted diagnosis of pediatric scurvy from clinical, laboratory, radiologic examination and excellent response after vitamin C supplementation. Results: A 3-year-old boy presented with 2 months of painful edematous knees and feet and pseudoparalysis, 11 days of palpable perifollicular petechiae and corkscrew hairs on legs, and 3 days of petechiae on feet and edematous easily-bleeding gingiva. His diet lacked fruit and vegetables. Laboratory showed anemia, elevated erythrocyte sedimentation rate, decreased iron, and hematuria. Knees’ plain radiograph showed osteopenia and joint effusion. Initial assessment was cutaneous vasculitis. Complaints persisted despite treatment with ibuprofen and prednisone, but improved rapidly after vitamin C supplementation. Histopathology of skin lesion showed no vasculitis. Final diagnosis was scurvy. Vitamin C supplementation was continued with noted resolution and no recurrence of signs and symptoms. Conclusions: Prominent musculoskeletal findings and vasculitis-like skin lesions often cause misdiagnosis of pediatric scurvy. Perifollicular petechiae, corkscrew hairs, gingival edema, and dietary history were clues for scurvy. Diagnosis of scurvy can be established by clinical and supporting examination, or in ex juvantibus, when ascorbic acid level measurement is unavailable.